THE RELEVANCE OF THE MERDEKA BELAJAR POLICY WITH THE DEMANDS FOR DIGITIZING EDUCATION IN INDONESIA - Akhmad Aji Pradana; Nurhaningtyas Agustin; Mayada Izzatul A'yun; Nina Septiana (International Conference on Social and Islamic Studies, 2021)
This article aims to examine the policy of merdeka belajar which is considered suitable to be applied in the era of digitalization that brings democracy of knowledge. The focus of the study in this research is the policy of merdeka belajar and digitalization of education which is using a qualitative approach with the type of Library Research, the literacy collected is extracted from online journal articles sources that are relevant to the research focus in the last 10 years. After going through data reduction, content analysis, it can be concluded that the independent learning policy is considered relevant to the demands of digitalization of education in Indonesia.